Evaluation of bank windu kentjana regarding merger plan in acquiring bank antardaerah - Gara, Surya; Salamantun Zen, Tuntun (The Indonesian Journal of Business Administration, 2016)
Abstract. According to the annual report 2015, Bank Windu is reported that they would purchase 1,002,500 total shares or 100% capitalization of Bank Antardaerah. Later on Bank Antardaerah would be fully absorbed by Bank Windu. Both Banks already signed the Conditional Sales and Purchase Agreement on July 1, 2015. The business issue that become the focus here is the discussion regarding evaluation on merger plan that would be executed by Bank Windu by considering the benefit through valuation process and risk that would be arised. This research is analyzed thorugh 3 explorative studies focused on internal environment analysis that using resources and capabilities. Environment analysis that using PEST and Porter Five Forces. Merger analysis that search the processess and motives from this merger plan. 3 of those explorative studies shows that by executing merger plan Bank Windu would be able to face the current economic situation and more prepared in the future compeitition.  From this research, Bank valuation is conducted by using theory of excess equity return for both banks and also merger plans. The result shows that The real value of Bank Antardaerah is Rp. 209,199,399,886 while the book value is Rp. 160,331,000,000 or 1.3 times, the real value of Bank Windu is Rp. 1,386,753,146,849 while the book value is Rp. 653,629,000,000 or 2.12 times. On the other hand, there are three merger scenarios here. Optimistic scenario that resulted merger value of Rp. 1,612,983,541,090. Most Likely scenario that resulted merger value of Rp. 1,595,952,546,735 and pesimistic scenario that resulted merger value of Rp. 1,526,893,729,402. The maximum potential gain (synergy) from this merger is Rp. 17,030,994,355 and the maximum potential loss (synergy) is - Rp. 69,058,817,333. While, the maximum price with net profit Rp. 0 for Bank Windu in purchasing Bank Antardaerah is Rp. 226,230,394,240. In term of risk there are 3 low risks, 5 medium risks and 1 high risk that possible to arised, but by using COSO risk framework. The risks are possible to be mitigated and decreased into 5 low risks, 3 medium risks and 1 high risk. The conclusion from this research is the Bank Windu merger plan is very possible and recommended to be executed.      Keywords: Bank Windu, Bank Antardaerah, Merger, Valuation, 3 Scenario Calculations and Risk